A - Weston, Anthony (Oxford University Press, 2002)
A Practical Companion to Ethics, 2/e, is a concise and accessible introduction to the basic attitudes and skills that make ethics work, like thinking for oneself, creative and integrative problem-solving, and keeping an open mind. This unique volume illuminates the broad kinds of practical intelligence required in moral judgment, complementing the narrower theoretical considerations that often dominate ethics courses. It offers practical instruction in problem-solving by demonstrating how to frame an ethical problem and deal effectively with ethical disagreements. This book also addresses issues of the heart--the call to responsiveness and care that underlies formal ethical theories. The appendix offers an extended and specific guide to writing papers in ethics